2021
DOI: 10.1007/s00170-021-07472-x
|View full text |Cite
|
Sign up to set email alerts
|

New drawbead tester and numerical analysis of drawbead closure force

Abstract: Currently, a great deal of controversy exists regarding the real forces generated in drawbeads during sheet metal forming processes. The present work focuses on the analysis of the uplift force. First, a detailed literature review is carried out to analyse previous experimental procedures used to measure uplift forces. It is found that previous setups do not perfectly replicate the real geometry of industrial drawbeads. In order to obtain reliable forces, an experimental drawbead tester capable of adequately r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…It was concluded that when a higher force was applied to the draw bead, a higher restraining force was generated. Gil et al [26] proposed a model to identify the main variables affecting the uplift force in the drawbead region. They found that minor geometrical deviations in the drawbead geometry significantly affect the uplift force.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that when a higher force was applied to the draw bead, a higher restraining force was generated. Gil et al [26] proposed a model to identify the main variables affecting the uplift force in the drawbead region. They found that minor geometrical deviations in the drawbead geometry significantly affect the uplift force.…”
Section: Introductionmentioning
confidence: 99%
“…In order to determine the friction and wear of materials, the following types of tests and tribometers may be used: (a) strip drawing test with flat [ 19 , 20 ] and (b) rounded [ 21 ] (c) countersamples, (d) bending-under-tension test [ 22 , 23 ], (e) draw-bead test [ 24 , 25 ], and (f) ball-on-disc [ 26 ], (g) block-on-disc [ 27 ], (h) pin-on-ring [ 28 ], and (i) pin-on-disc tribometers [ 29 , 30 ]. Most of the studies, the results of which can be found in the literature, indicate the susceptibility of aluminium sheets to galling and intensification of the flattening mechanism.…”
Section: Introductionmentioning
confidence: 99%